South Korea’s Response to the Myanmar Military Coup in 2021 - LEE, JOUNG-JUN; BAK, CHEON-SU; JANG, JUN-HO; KIM, HO-WOOG; CHUNG, JUN-KI (The journal of contemporary issues in business and government, 2021)
On 1 February, 2021, on the grounds that the 2020 election was fraudulent in nature, Myanmar's military launched a coup and declared martial law, arresting major government leaders. Myanmar citizens have protested the coup through a movement of civil disobedience. The military, in turn, mobilized soldiers and police to curb the protests with force. The U.S. and South Korea immediately demanded that the military release the arrested government personnel, including Aung San Suu Kyi, whose reputation as a peacemaker and Nobel Prize winner had been tarred by her handling of the Rohingya refugee crisis in 2017. Among East Asian countries, South Korea is the only one wherein thousands of people, including President Moon Jae-in, have demonstrated their support for Myanmar's democratic movement. This study aims to understand why South Korea is alone among East Asian countries in their support of Myanmar's democratic movement. Additionally, we will investigate some crucial, socio-political implications underlying this support.